Peculiarities of Predicting Business Cycles in the Ukrainian Economy - Puhachova, M. V. (Statistics of Ukraine, 2019)
It is argued in the article that any common person is able to get an idea about the economy’s conditions and its forthcoming change, if he/she learns information Business Tendency Surveys (BTS), i. e. with combination indicators computed on the basis of indicators from these surveys. A review of the methods for constructing several types of integral composite indicators, based on indicators of BTS of enterprises by selected economic activities, is provided. Indicators of business climate, computed by the methodology of ifo-Institute and European Commission, and indicators of confidence by economic activity are analyzed. Being ahead of the curve, these indicators give good signals on change in the phases of business activity cycles in European economies and allow one to have rather precise short-term predictions of change in GDP and output by economic activity. The analysis covers dynamic series of these indicators for the Ukrainian economy, with making the conclusion that now only the indicators of confidences for four economic activities can be used for predicting the business cycle for 2 to 3 quarters. The Business Climate Indicator, computed by the European methodology, has good correlation with GDP, but it is only one quarter ahead of it. The Business Climate Indicator, computed by the methodology of ifo-Institute, did show rather good correlation with GDP, but could not demonstrate its good qualities as for the German economy. Unfortunately, this indicator could be computed only for the period before 2013, because subsequently its components were withdrawn from survey questionnaires. One of the main recommendations given in the article is as follows: an organization performing BTS of enterprises (namely, the State Statistics Service of Ukraine) needs to more actively propagate the information about various composite indicators that can obviously be demanded by a broad range of statistical information users. These indicators should be, inter alia, displayed on the home page of the official web-site of the State Statistics Service of Ukraine together with hot news (probably, in a graph form together with macroeconomic indicators).